Eating habits, nutritional status and obesity in students of Gastronomy and Business Management - A. Cerna, Jorge (2024)
Eating habits influence nutritional status and obesity in students of Gastronomy and Business Management at Le Cordon Bleu University, according to what was studied in this research and considering the nature of the study, a quantitative approach was taken, it was substantive. or basic, with a descriptive correlational design and hypothetical deductive method. The study sample consisted of 35 students. The technique used was the survey, and where questions oriented to the three dimensions proposed for this research were included; These instruments, which were aimed at gastronomy and Business Management students of the sixth cycle, allowed the respective information to be collected: Questionnaire on eating habits and nutritional status and it was concluded that there is a significant relationship between eating habits and nutritional status and nutritional status and obesity, the which are observed in a greater proportion at the medium and high levels and allow us to establish the significant relationship between eating habits and nutritional status, as well as the significant relationship between nutritional status and obesity; The results are very interesting to define the eating habits of students of Gastronomy and Business Management.